Nicotine-free electronic vape fluid stimulates angiogenic processes in vitro through ARF6-mediated oxidative stress - Spurrier-Best, Lewis; Butcher, David; Blackham-Hayward, Evangelene; Kertesz, Zsuzsanna; Chichger, Havovi (Frontiers in Toxicology, 2026)
IntroductionThe increase in e-cigarette use in the population has led to substantial interest in the health impacts associated with e-cigarette smoking. E-cigarette smoking represents a key external environmental cell stressor. Whilst there have been several studies to investigate the effect of nicotine-containing e-cigarette fluid, there is still a significant lack of understanding of how nicotine-free e-cigarette smoking can impact individuals. However, preliminary studies indicate that nicotine-free e-cigarette smoking can cause impaired endothelial function in humans.Materials and MethodsIn the present study, we therefore used a common brand of nicotine-free e-cigarette and human umbilical vein endothelial cells to assess angiogenic processes in vitro.ResultsWe observed a significant upregulation in endothelial cell adhesion, migration and new tube formation with exposure to nicotine-free e-cigarette condensate (eVape) which was abrogated with exposure to the antioxidant, N-acetyl cysteine. Proteome analysis demonstrated that eVape exposure increased expression of the pro-angiogenic factors, angiogpoeitin-2, endoglin (CD105), PIGF and VEGF, as well as the ADP ribosylation factor, ARF6, and ARF6-GEF, ARNO. Chemical inhibition of ARNO reduced eVape-induced oxidative stress, angiogenic processes, and release of angiogpoeitin-2, endoglin (CD105) and VEGF.DiscussionThese findings demonstrate that nicotine-free eVape causes aberrant upregulated angiogenesis in an in vitro model of the human endothelium through ARNO-dependent signalling. This study is the first to demonstrate the molecular mechanisms in response to the cellular stressor, nicotine-free eVape which underlie impaired vascular function.